2006
DOI: 10.7498/aps.55.704
|View full text |Cite
|
Sign up to set email alerts
|

Information entropy squeezing of the atom of an arbitrary initial state via the two-photon process

Abstract: From the quantum information point of view we investigate the entropy squeezing properties of a two_level atom with arbitrary initial state interacting with the coherent field via the two_photon process. The influence of the initial state of the system on the atomic information entropy squeezing is discussed. The numerical results obtained from the uncertainly relation of quantum information entropy are compared with those obtained from the uncertainly relation of Heisenberg. It is shown that the number of sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This corresponds to the result obtained in Ref. [16]. Thus we focus the attention on the discussion of E(S y ) (the entropy squeezing of the component S y ) by a numerical calculation method.…”
Section: The Atomic Entropy Squeezingsupporting
confidence: 79%
“…This corresponds to the result obtained in Ref. [16]. Thus we focus the attention on the discussion of E(S y ) (the entropy squeezing of the component S y ) by a numerical calculation method.…”
Section: The Atomic Entropy Squeezingsupporting
confidence: 79%
“…[6], and correspond to the results obtained in Ref. [7]. Figure 2 presents the numerical results of the time evolution of E(S y ) for different initial states of the two atoms with p = 1, φ = π, and n = 36.…”
Section: Atomic Entropy Squeezingmentioning
confidence: 56%
“…[15] Several authors found an elegant entropic way of reformulating the HUR by using quantum entropy theory, and obtained an entropic uncertainty relation (EUR), which could be free from the triviality of the HUR. [7,16,17] Quantum entanglement is one of the most strik-ing features of quantum mechanics. It has been recognized as a resource in quantum information processing [19] and quantum computing.…”
Section: Introductionmentioning
confidence: 99%
“…[22] This difficulty has been overcome by using the entropy uncertainty relation (EUR). [23,24] The entropy squeezing effect of atoms has been studied in many other systems, such as the two-photon JCM, [25] JCM in a nonlinear medium, [26,27] and two-atom JCM. [28] More recently, much interest has been aroused in entropy squeezing and entanglement in solid-state circuit QED, [29−31] in which a nano-resonator serves as a cavity.…”
Section: Introductionmentioning
confidence: 99%